Coach Dionisio Calvo was newly designated coach of the 1959 De La Salle NCAA basketball team - De La Salle University, Manila (Animo Repository, 1959)
Coach Dionisio (Chito) Calvo was newly designated Coach of the 1959 De La Salle NCAA Basketball Team. Calvo first handled the Green Archers in 1929. He left LS after 2 years and came back in 1935. He was responsible for giving LS the NCAA crown in 1939, which was duplicated in 1947.